A imagem do burocrata insatisfatório: Uma apreciaç\~ao - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The 'Image of the Unsatisfactory Bureaucrat' portrays a mischief as socially and culturally uniform. It gives the impression that the inconveniences, nuisances or frustrations in dealing with State agencies would have a one-cause explanation, i.e., traits of personality or conduct of the bureaucrats. However, an organizational mischief has alternative explanations. Among them, the mode of management in State agencies is affected by the criterion of political-partisan convenience in the choice of managers; the organizational structure of these agencies is shaped by the fact that the State looks after the social order; in several agencies, the form of administration is the command and control regime; and sometimes the endowment of resources is meager, which induces State agencies to operate with rationing by waiting.
Keywords: D73; A13; B40; 330; unsatisfactory bureaucrat; State agencies; organizational explanation; political-partisan criterion; rationing by waiting